![image](https://tex.z-dn.net/?f=lim%28x%20-%20%3E%204%29%20%5Cfrac%7B3%20%7Bx%7D%5E%7B2%7D%20-%2014x%20%2B%208%20%7D%7B4%20%2B%207x%20-%202%20%7Bx%7D%5E%7B2%7D%20%7D%20%20%3D%20%20%7C%20%5Cfrac%7B0%7D%7B0%7D%20%7C%20%20%3D%20lim%28x%20-%20%20%3E%204%29%20%5Cfrac%7B%28x%20-%204%29%28%20x%20-%20%20%5Cfrac%7B2%7D%7B3%7D%29%20%7D%7B%28x%20%2B%20%20%5Cfrac%7B1%7D%7B2%7D%29%28x%20-%204%29%20%7D%20%20%3D%20lim%28x%20-%20%20%3E%204%29%20%5Cfrac%7Bx%20-%20%20%5Cfrac%7B2%7D%7B3%7D%20%7D%7Bx%20%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%20%3D%20%20%5Cfrac%7B4%20%20-%20%20%20%5Cfrac%7B2%7D%7B3%7D%20%7D%7B4%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%7D%20%20%3D%20%20%5Cfrac%7B10%7D%7B3%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%7D%7B13%7D%20%20%3D%20%20%5Cfrac%7B10%7D%7B13%7D%20)
4) \frac{3 {x}^{2} - 14x + 8 }{4 + 7x - 2 {x}^{2} } = | \frac{0}{0} | = lim(x - > 4) \frac{(x - 4)( x - \frac{2}{3}) }{(x + \frac{1}{2})(x - 4) } = lim(x - > 4) \frac{x - \frac{2}{3} }{x + \frac{1}{2} } = \frac{4 - \frac{2}{3} }{4 + \frac{1}{3} } = \frac{10}{3} \times \frac{3}{13} = \frac{10}{13} " alt="lim(x - > 4) \frac{3 {x}^{2} - 14x + 8 }{4 + 7x - 2 {x}^{2} } = | \frac{0}{0} | = lim(x - > 4) \frac{(x - 4)( x - \frac{2}{3}) }{(x + \frac{1}{2})(x - 4) } = lim(x - > 4) \frac{x - \frac{2}{3} }{x + \frac{1}{2} } = \frac{4 - \frac{2}{3} }{4 + \frac{1}{3} } = \frac{10}{3} \times \frac{3}{13} = \frac{10}{13} " align="absmiddle" class="latex-formula">